If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -48 + 48x = 336 Solving -48 + 48x = 336 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + 48x = 336 + 48 Combine like terms: -48 + 48 = 0 0 + 48x = 336 + 48 48x = 336 + 48 Combine like terms: 336 + 48 = 384 48x = 384 Divide each side by '48'. x = 8 Simplifying x = 8
| 21/100x28 | | w(w)-144=0 | | 6x-3x+4-2x=2x+1 | | 1/6x=21/8 | | 6x-3x+4-2x=1x+3 | | -25=3/4x-6 | | 3/5f-4/5=8/5 | | 4ax(3a+3z+9ax)= | | (B-3)-7= | | 5x+3x+6=3x+16 | | 50=0.19*x | | 100-20q=1-400/q^2 | | 2+-3(x+4)=9+-(3+2x) | | x/11-4=11 | | 5y-14=2y-7 | | 4x+1x+32=2x+56 | | 20q^3-99q^2-400=0 | | c(c)+5c-36=0 | | 50=0.16*x | | x(x)-x-42=0 | | 4x+70=18x | | =16x+20xy | | 50=0.13*x | | 5c(c)+5c-60=0 | | 2a(a)+6a=20 | | g(g)+9g+18=0 | | 4x-x=40.12 | | 2/9v-4/2=2 | | 7z-7=z+17 | | -16t^2+8t+48=.25 | | http://b/1.3-5.4=1.8 | | Y-1.2=5.85 |